Expression of NKp46 Splice Variants in Nasal Lavage Following Respiratory Viral Infection: Domain 1-Negative Isoforms Predominate and Manifest Higher Activity - Shemer-Avni, Yonat; Kundu, Kiran; Shemesh, Avishai; Brusilovsky, Michael; Yossef, Rami; Meshesha, Mesfin; Solomon-Alemayehu, Semaria; Levin, Shai; Gershoni-Yahalom, Orly; Campbell, Kerry S.; Porgador, Angel (Frontiers in Immunology, 2017)
Abstract- The natural killer (NK) cell activating receptor NKp46/NCR1 plays a critical role in elimination of virus infected and tumor cells. The NCR1 gene can be transcribed into five different splice variants, but the functional importance and physiological distribution of NKp46 isoforms are not yet fully understood. Here we shed light on differential expression of NKp46 splice variants in viral respiratory tract infections and their functional difference at the cellular level. NKp46 was the most predominantly expressed NCR in the nasal lavage of patients infected with three respiratory viruses: respiratory syncytia virus, adenovirus, human metapneumovirus, or influenza A. Noticeable correlations were observed between expression of NKp46 and IFN-γ or TNF-α, which indicates strong infiltration of and cytokine production by NK cells within the respiratory tract after viral infection. Expression of NKp30 was far lower and NKp44 was absent in all patients. Domain 1-negative NKp46 splice variants (i.e. NKp46 isoform d) were the predominantly expressed isoform in nasal lavage following viral infections. Using our unique anti-NKp46 mAb, D2-9A5, which recognizes the D2 extracellular domain, and a commercial anti-NKp46 mAb, 9E2, which recognizes D1 domain, allowed us to identify a small subset of NKp46 D1-negative splice variant-expressing cells within cultured human primary NK cells. This NKp46 D1-negative subset also showed higher degranulation efficiency in term of CD107a surface expression. NK-92 cell lines expressing NKp46 D1-negative and NKp46 D1-positive splice variants also showed functional differences when interacting with cancer cell. A NKp46 D1-negative isoform-expressing NK-92 cell line showed enhanced degranulation activity. To our knowledge, we provide the first evidence showing the physiological distribution and functional importance of human NKp46 splice variants under pathological conditions.